Mesenchymal stem cell transplantation plays a role in relieving cancer pain - Zhang, Wen-Jun; Chen, Dingyi (Frontiers in Pharmacology, 2024)
Tumors can invade, compress, and damage nerves, leading to persistent pain and seriously affecting the quality of life of patients. However, their treatment is challenging. Sensitization of peripheral receptors, abnormal activity of primary sensory neurons, activation of glial cells, enhanced inflammatory responses, and sensory information transmission contribute towards cancer pain. Therefore, considerable attention has been paid to exploring prospective methods to inhibit the occurrence of these factors and relieve cancer pain. Studies on different types of pains have revealed that the transplantation of functionally active cells into the host has the pharmacological effect of producing analgesia. Mesenchymal stem cells (MSCs) can act as small active pumps to reduce the expression of pain-related molecules and produce analgesic effects. Moreover, MSCs can establish complex communication networks with non-tumor and cancer cells in the microenvironment, interact with each other, and can be used as destinations for inflammation and tumor sites, affecting their potential for invasion and metastasis. This emphasizes the key role of MSCs in cancer and pain management. The pain relief mechanisms of MSCs include neuronutrition, neural protection, neural network reconstruction, immune regulation, and improvement of the inflammatory microenvironment around the nerve injury. All of these are beneficial for the recovery of injured or stimulated nerves and the reconstruction of neural function, and play a role in relieving pain. The pain treatment strategy of cell transplantation is to repair injured nerves and produce analgesic pharmacological properties that are different from those of painkillers and other physiotherapies. Although the therapeutic role of MSCs in cancer and pain is in its early stages, the therapeutic value of MSCs for cancer pain has great prospects. Therefore, in this study, we explored the possible mechanism between MSCs and cancer pain, the potential therapeutic role of therapeutic cells in cancer pain, and some problems and challenges.